Determination of uranium internal dose exposure through soil digestion using RDRC and URODC software - Mohd Izwan Abdul Adziz,; Nor Amira Amalina Mohd Badri,; Khoo, Kok Siong (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was conducted to determine the dose of internal exposure through ingestion of soil in the vicinity of the repository facility in Bukit Kledang, Ipoh, Perak. Data from this study can assess the risk of radiation exposure to the health of local population, specifically blood, liver and bone cancers. Activities of radionuclide 238U in MG and M10 in the gastric phase are 1.118 ± 0.062 and 1.232 ± 0.073 Bq/kg, while the respective activities in the gastrointestinal phase are 0.553 ± 0.051 and 0.905 ± 0.082 Bq/kg. Samples of M10 recorded the highest reading of internal exposure in both phases. Digestion of 2 g soil from M10 samples on gastric phase generated the annual effective dose of 3.168 μSv/year with an assessment of cancer risk by 0.001% within 70 years to public. Organ dose for blood, liver and bone were 0.59, 11.60 and 65.95 μSv, respectively. Analysis of organ doses based on the concentration of 238U found that M10 has higher dose compared to MG. Risk assessment predicted for 70 years after the ingestion of the soil for blood cancer was 0.003% and liver cancer was 0.004% while the highest cancer risk was for bone cancer with 0.023%. Although the concentration of specific activity of 238U identified is low, it is shown that the internal dose exposure as a result of digestion of radionuclides are below the standard and can be considered as safe for public.